Mapping Potential Fishing Zones for Skipjack Tuna (Katsuwonus pelamis) Using Satellite Imagery - Angraeni, Angraeni; Sora Datu, Syeqido; Nurfaidah; Rahmatang (Aquaculture Department, University of Mataram, 2024)
Fisheries are an important economic sector for many countries, including Indonesia. Bone Bay has high potential for skipjack (Katsuwonus pelamis) fishing. This study aims to map potential skipjack fishing zones in Bone Bay and analyze the relationship between sea surface temperature, salinity, and chlorophyll-a concentration with the catch of these fish. Using quantitative methods and probability sampling techniques, primary data were obtained through direct observation of fishing activities using the pole and line method, while secondary data were obtained from satellite images downloaded from the Oceancolor website. The results showed that the potential zones for skipjack fishing are located at coordinates 3o0’0”LS-4o30’0”LS and 120o30’0”BT-121o0’0” BT. The findings are expected to help stakeholders make strategic decisions for more effective and susstainable fisheries management.